THE RUSSIAN ANESTHESIOLOGY AND CRITICAL CARE IN 2019 – WHAT WE HAVE ACHIEVED AND WHERE WE GO - Yu. S. Polushin (Вестник анестезиологии и реаниматологии)
Looking back at the 60-year period of anesthesiology and critical care development in this country, the author paid special attention to some considerations that largely reflect the ideology and psychology of specialists working in this field, who, from his point of view, interfered with further development of this specialty as an independent medical field in Russia. Special emphasis was put on some problematic issues of interdisciplinary interaction, training, and organization of care. It was noted that the experience of predecessors was to be taken into account since the essence of many current problems was in many ways the same as it had been before. The author suggested that moving forward was possible only if the efforts of the entire professional community were consolidated.